Standardization of a protocol for disinfection of leaf discs in the induction of callus formation of Cordia alliodora (Ruiz & Pav.) Oken (Lamiales: Boraginaceae) in vitro (Revista de Investigaciones Universidad del Quindío, 2010)
Cordia alliodora (Ruiz & Pav.) Oken, is a species with a dual purpose: commercial exploitation and the possibility of improving the environment because of its nutrients and its links with silvopastoral systems. The application of micropropagation techniques in forest species has been a useful alternative to increase the establishment of plantations. However, the disinfection of explants in these kind of species has been one of the limiting factors for establishment in vitro, due to the presence of pollutants that affect the performance of these species under in vitro conditions; making it necessary the use of disinfection protocols that allow the decrease in the appearance of pollutants. The objective of this research was to evaluate different protocols for disinfection of explants (leaf disc), to determine the efficiency in the smallest degree of contamination without compromising their viability. We evaluated three protocols: 1) López  2) Marulanda et al.  y 3) Ramírez – Villalobos  et al. although protocols 2 and 3 showed similar results statistically, the last one was chosen because it was the one that  compromised the least the viability of the explant.
Keywords: Cordia alliodora; leaf disc; disinfection protocols